English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

introduction to algebra

2007-01-18 08:33:02 · 3 answers · asked by needtutor07 1 in Science & Mathematics Mathematics

3 answers

x=12, y=6
x-y/3=12-6/3=10

2007-01-18 09:05:05 · answer #1 · answered by yonibak 2 · 0 0

if x is 12 then Y must be 6, divide so just follow pemdas rule. Parenthesis, Exponents, Multiply, add or subtract. Since there are no parenthesis you divide first, then you subtract. 12-6/3 comes to 12-2 which equals 10. Follow the orders of operation and you won't go wrong.

2007-01-18 08:43:01 · answer #2 · answered by Anonymous · 0 0

If you mean (x-y)/3, then (12 - 6)/3 = 2.
If you mean x - (y/3), then 12 - 6/3 = 10.

2007-01-18 08:36:32 · answer #3 · answered by Philo 7 · 1 0

fedest.com, questions and answers